Medical-Psychological Correction of Anxiety-Depressive Disorders in Systemic Lupus Erythematosus - N.M, Maxamatjanova; Z.R., Ibadullaev (International Journal of Psychosocial Rehabilitation, 2020)
According to a study’s date, psycho-emotional disorders in rheumatic diseases are caused by anxiety-depressive disorders, which are 7-15 times higher than in the general population and account for 89%. [1,6,7.] According to recent data, the prevalence of depression in patients diagnosed with systemic lupus erythematosus is on average 47% [3]. According to other scientists, depressive episodes accounted for 27%, and dysthymia was identified as a manifestation of these depressive disorders. Mild depressive mood that lasted for more than 2 years was observed in 6% of patients, adaptation disorders were detected in 16%, and generalized anxiety disorders in 7% of patients. Overall, anxiety-depressive disorders were detected in more than half (56%) of the patients [4,5]. Therefore, the diagnosis of anxiety-depressive disorders in patients with systemic lupus erythematosus requires the use of psychopharmacotherapy. However, the use of psychotropic drugs alone, along with basic treatment, is not effective enough. Facilitating the course of the disease requires patients to use psychotherapy in order to improve their quality of life. The purpose of the study: to study and estimate medical-psychological correction of anxiety-depressive disorders in systemic lupus erythematosus.